Impact of ankylosing spondylitis on foot health and quality of life: an observational case–control study - Cortes-Rodríguez, Antonio; Alves-Gomes, Lisa; Losa-Iglesias, Marta Elena; Gómez-Salgado, Juan; Becerro-de-Bengoa-Vallejo, Ricardo; Saavedra-García, Miguel Ángel; Montiel-Luque, Alonso; López-López, Daniel; Jiménez-Cebrián, Ana María (Frontiers in Medicine, 2024)
Background Ankylosing spondylitis (AS) is a chronic, inflammatory, and autoimmune disease. This condition primarily affects the axial skeleton and presents direct foot involvement, such as Achilles enthesitis or plantar fascia involvement. Objective This study aimed to investigate the impact of foot health on the quality of life of individuals with AS compared to a control group without AS. Materials and methods A sample of 112 subjects was recruited, with a mean age of 46.80 ± 10.49 years, divided into two groups: 56 individuals with AS (cases) and 56 individuals without AS (controls). Demographic data were collected, and the scores obtained in the Foot Health Status Questionnaire domains were recorded. Results Of the participants, 27.79% (N = 30) were men and 73.21% (N = 82) were women. The mean age in the group was 46.80 ± 10.49. Significant differences (p < 0.05) were found in the domains of foot function, foot pain, footwear, overall foot health, general health-related physical activity, and social capacity between the AS group and the control group. Conclusion Individuals with AS exhibited a decreased quality of life, as indicated by their Foot Health Status Questionnaire scores.